Partial resection of large congenital left ventricular diverticulum in an infant: a case report - Yibing Fang; Qi An; Tianping Yu; Shuhua Luo (BMC Surgery, 2020)
Abstract Background Congenital left ventricular diverticulum is a rare cardiac malformation usually requiring total resection. Case presentation This report describes an infant presenting with a large apical diverticulum with a wide ventricle connection. Given the vicinity of the left anterior descending coronary artery to the diverticulum and its wide ventricular connection, partial resection was undertaken. The patient remained asymptomatic with good heart function 8 months after surgery. The last follow-up echocardiography did not demonstrate any significant left ventricular outpouching. Conclusions We advocate early treatment of left ventricular diverticulum in children given the risk of spontaneous rupture of diverticulum, sudden death, and other serious complications if left untreated. For small patients with a wide connection of diverticulum to ventricle, partial resection is a safe option with favorable short-term outcomes.